Study of pulmonary function test in different trimester of pregnancy - Vandana B Dudhamal; Smita Parate (International Journal of Medical Research and Review, 2015)
Introduction: Pregnancy is characterized by sequence of dynamic physiological changes that impact on multiple organ system functions and is associated with various changes in pulmonary anatomy and physiology. The aim of the study was to see whether any changes occur in pulmonary function tests in the three trimesters of pregnancy as compared with that of’ control group.Material & Methods: A case control study of the pulmonary function tests were carried out in different trimester of pregnancy, on 70 normal pregnant women from 16 to 30 years attending antenatal clinic at Govt. Medical College, Nanded. Four respiratory parameters FVC, FEV1, FEV3, MVV & PEFR were determined in both, 70 pregnant women as cases & control group of 30 non-pregnant women of same age groups, Using computerized Medspiror instrument.Results: Expiratory Reserve Volume (ERV) and mean residual Volume (RV) in the pregnant subjects as the pregnancy advances reaching its maximum decrease by the end of III trimester. Mean Tidal Volume progressively increased as pregnancy advances reaching its maximum value at term , there is a gradual increase in the mean Minute Volume (MV) of the pregnant subjects as they proceed to term when compared with the controls. The mean Vital Capacity (VC) of the subjects in the I trimester pregnancy showed a non significant increase of 3.48 % The same parameter relating to the subjects in the II and III trimester pregnancy showed a statistically significant increase of 3.50 % and 8.60% respectively as compared with control subjects.Conclusion: Comparative study of pulmonary function tests on different trimesters of pregnancy showed that respiratory parameters were significantly compromised during pregnancy, There were decrease in respiratory parameters from first to third trimesters of pregnancy may be due to poor nutrition because all the subjects coming from middle class and poor socio-economic status